The Contribution of Bible Reading Habits to Finding Meaning in Life: A Study of Young Evangelicals in Norway - Zeiffert, Roald (Journal of European Baptist Studies, 2024)
Drawing from both quantitative and qualitative data, this mixed-method article investigates how reading the Bible contributes to a meaningful life for young evangelicals in Norway. The analysis shows that three groups emerge from the data. The Coherent group regularly read the Bible and find it important for how they live their lives. Bible reading is an integrated part of their lives; they often read together with their peers and use the Bible as an important source of meaning. Members of the Frustrated group find the Bible important for their lives but read less. They experience a stressful, conflicted relationship with the Bible and a weaker experience of meaning. Those in the third group, the Distanced, do not find the Bible very important, or read it very often; for them, the Bible is neither a source of meaning nor a source of frustration. They do not seek meaning from the Bible.